Hypericum japonicum extract inhibited porcine epidemic diarrhea virus in vitro and in vivo - Rao, Hongyu; Su, Weiwei; Zhang, Xiaoli; Wang, Yonggang; Li, Tao; Li, Jinliang; Zeng, Xuan; Li, Peibo (Frontiers in Pharmacology, 2023)
Porcine epidemic diarrhea virus (PEDV) infection causes lethal watery diarrhea and high mortality in neonatal piglets, leading to huge economic losses in the global swine industry. Currently, the existing commercial vaccines are not fully control PEDV, so it is urgent to develop effective antiviral agents to complement vaccine therapy. In the present study, we investigated the antiviral effect of Hypericum japonicum extract (HJ) against PEDV in vivo and in vitro. In vitro assays, HJ could directly inactivate PEDV strains, moreover, it inhibited the proliferation of PEDV strains in Vero or IPI-FX cells at its non-cytotoxic concentrations. Time of addition assays revealed that the HJ mainly inhibited PEDV at the later stages of the viral life cycle. In vivo, compared with the model group, HJ could reduce the viral titers in the intestines of infected piglets, improve their intestinal pathological changes caused by PEDV, and protect the newborn piglets from highly pathogenic PEDV variant infection, indicating that HJ can effectively inhibit PEDV infection. Furthermore, this effect may be related to the fact that HJ can not only directly inhibit viruses, but also regulate the structure of intestinal microbiota. In conclusion, our results indicate that hypericum japonicum could inhibit PEDV replication in vitro and in vivo, and might possess the potential to develop as the anti-PEDV drug.